AKULTURASI BUDAYA JAWA TERHADAP PENDIDIKAN AGAMA ISLAM (Studi Kasus Tradisi Tingkepan di Desa Wonorejo Kecamatan Kedunggalar Kabupaten Ngawi) - Laila Nisfatut Tarwiyah; Rosichin Mansur; Muhammad Sulistiono (VICRATINA, 2019)
Most Muslims, especially the people in Wonorejo Vilage, do not know thr meaning and value of education contained in the front culture. Especially nowaday we find many people who argue that something not taught at the time of the prophet is called bid’ah. If there is no acculturation beetwen Islamic culture and teachings, it is feared that there is a notion that the traditional ceremonies out of the values of Islamic aqeedah are because these cultures are not found in the Qur’an and Hadith. Even if we learn more about the many teachings, even though the names used are still names in Javanese customs, the values  contained in them have been replaced with Islamic values by Walisongo. The type of research used is qualitative. The approach used is a case study. The results of this study are the leading tradition in Wonorejo Village, Kedunggalar Sub-district, Ngawi District, including:splasing of ivory coconut, wearing cloth seven times alternately, salvation program. The foods in the traditional tradition in Wonorejo Village are sego golong, Holy sekol, ikung, banan setangkep, sego rogoh, segi asahan, market snacks, jenang merah putih, waluh, and buceng pitu. The leading tradition ini Wonorejo Village is not in conflict with islamic teachings because in it there are values of Islamic religius educations.  Keywords: Acculturation, Javanese Culture (Tingkepan), Islamic Religious Education